Theoretical study on wear characteristics of single screw refrigeration compressor with multicolumn envelope meshing pair. (June 2019) - Wang, Zengli; Wang, Hao; Wang, Jun; Li, Qiang; Feng, Quanke
Highlights: Theoretical model was established to predict the wear characteristics of SSRC. Theoretical model was validated by experimental and engineering survey data. Wear characteristics of the SSRC with MEMP have been analyzed. Optimization design principle of meshing pair profile parameters was obtained. Abstract: In single screw refrigeration compressor (SSRC), the wear of meshing pair has always been a key issue that restricts its development. In order to solve this problem, a Multicolumn Envelope Meshing Pair (MEMP) was proposed. However, the theoretical research on wear resistance of MEMP has not been carried out yet. Therefore, in this paper, a theoretical calculation model describing the influence of the MEMP profile parameters on wear characteristics of the SSRC with MEMP is established to predict the wear resistance. The presented model is verified as a powerful tool for wear characteristics analysis by the experimental results. With the validated model, the effect of MEMP profile parameters on the wear characteristics of SSRC has been analyzed. Optimization analysis shows that in the design stage more envelope columns with a larger center distance and larger envelope column diameter should be chosen for the MEMP to get a better wear resistance.